Central Bank Digital Currency (CBDC) Sebagai Alat Pembayaran di Indonesia - Claudia Saymindo Emanuella (Faculty of Law, Universitas Airlangga, 2021)
AbstractTechnological developments encourage innovation in various sectors, including banking. The widespread use of digital currencies is an impetus for central banks to create an alternative to replace ungoverned digital currencies. Central Bank Digital Currency (CBDC) is the alternative chosen by various central banks in the world. Various countries have conducted research related to the implementation in terms of design and risk in the financial, operational, and legal fields. Bank Indonesia plans to develop a CBDC as part of national economy and finance digitalization. Indonesia does not yet have a strong legal framework to underlie the implementation of CBDC, especially in the cyber security sector, The role of the central bank becomes very important in CBDC’s issuance and implementation as the only party that has the right to determine, issue, and regulate legal payment instruments in Indonesia.Keywords: Central Bank Digital Currency; Digital Money; Central Bank; Cybersecurity.AbstrakPerkembangan teknologi mendorong inovasi dalam berbagai sektor, termasuk perbankan. Maraknya penggunaan digital currency menjadi dorongan bagi bank sentral untuk menciptakan mata uang digital yang dapat menggantikan digital currency tanpa pihak berwenang. Central Bank Digital Currency (CBDC) menjadi alternatif yang dipilih oleh berbagai bank sentral di dunia, dan berbagai negara telah melakukan riset terkait penerapan CBDC dari sisi desain dan risiko di bidang finansial, operasional, dan legal. Bank Indonesia berencana untuk mengembangkan CBDC di Indonesia sebagai bagian dari digitalisasi ekonomi dan keuangan nasional. Indonesia belum memiliki kerangka hukum yang kuat untuk mendasari penerapan CBDC, terutama dalam bidang keamanan siber, mengingat banyaknya ancaman keamanan siber canggih yang terus berkembang. Peran bank sentral menjadi sangat penting dalam penerbitan dan penerapannya sebagai satu-satunya pihak yang berhak menentukan, menetapkan, menerbitkan, dan meregulasi alat pembayaran sah di Indonesia.Kata Kunci: Central Bank Digital Currency; Uang Digital; Bank Sentral; Cybersecurity.